Employment of Traditional Folk Arts in Omani Theatre: Razha and Al-Nairuz by Abdullah Al-Battashi as a Model (The International Journal for Scientific Research, 2025)
Folklore is rich in its various elements, and diverse in its rich contents of heritage material and its topics, and is classified in turn into four elements: popular beliefs, popular customs, folk arts, and folk literature. This research is concerned with employing folk singing arts in Omani theater, where employing folklore in Omani theater occupies an important space, and writers have been interested in employing it as a style and material discourse, and have worked to employ it and produce new connotations through dramatic treatments and projections that dealt with the vocabulary of folklore, especially folk tales and folk songs.The research focuses on the features of employing traditional folk arts in Omani theater, and explaining the features of this employment, and its impact on the theatrical work. The texts of the writer Abdullah Al-Batashi were chosen as a research model to answer the following questions:·     What are the features of employing heritage represented in traditional folk arts in Abdullah Al-Batashi's theatrical texts?·     What are the subjective and objective motives for the writer to invoke folk arts and employ them artistically and visually in the theatrical text?·     What is the artistic and literary value that this employment added to the theatrical text?·     What is the impact of this employment in enhancing the presence of traditional folk heritage in Omani theatre?
Keywords: Heritage; Folk Arts; Employment; Omani Theatre